2020
DOI: 10.1038/s12276-020-0374-4
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological inhibition of mTOR attenuates replicative cell senescence and improves cellular function via regulating the STAT3-PIM1 axis in human cardiac progenitor cells

Abstract: The mammalian target of rapamycin (mTOR) signaling pathway efficiently regulates the energy state of cells and maintains tissue homeostasis. Dysregulation of the mTOR pathway has been implicated in several human diseases. Rapamycin is a specific inhibitor of mTOR and pharmacological inhibition of mTOR with rapamycin promote cardiac cell generation from the differentiation of mouse and human embryonic stem cells. These studies strongly implicate a role of sustained mTOR activity in the differentiating functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Treatment of MSCs with rapamycin for 24 h significantly alleviated cellular senescence, which was accompanied by reduced ROS production and the downregulation of p-Jun N-terminal kinases (JNK) and p-38 27 . Our previous study also demonstrated that chronic inhibition of mTOR by rapamycin attenuated cellular senescence and markedly improved the functions of hCSCs 14 . As shown in this study, we demonstrated that MHY-1685 also inhibited mTOR signaling in hCSCs, resulting in a higher cellular survival rate in the presence of oxidative stress, an increased proliferation rate with a short cell population doubling time, and the sustained stemness with differentiation potential.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Treatment of MSCs with rapamycin for 24 h significantly alleviated cellular senescence, which was accompanied by reduced ROS production and the downregulation of p-Jun N-terminal kinases (JNK) and p-38 27 . Our previous study also demonstrated that chronic inhibition of mTOR by rapamycin attenuated cellular senescence and markedly improved the functions of hCSCs 14 . As shown in this study, we demonstrated that MHY-1685 also inhibited mTOR signaling in hCSCs, resulting in a higher cellular survival rate in the presence of oxidative stress, an increased proliferation rate with a short cell population doubling time, and the sustained stemness with differentiation potential.…”
Section: Discussionmentioning
confidence: 74%
“…Recent studies have reported that autophagy plays a role in the modulation of cell proliferation, differentiation, and senescence. Our previous study suggested that the autophagy inducer rapamycin reduced the senescence of hCSCs and improved cellular activities 14 . To establish whether MHY-1685 modulates autophagy signaling, we assessed the expression of an autophagy signal regulator protein (mTOR) by western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agreeing data were provided, indicating that these mTORC1 inhibitors operate via different mechanisms to inhibit the SASP, contributing to the up-regulation of DNA repair proteins and associated post-transcriptional modifications [ 174 , 176 ]. Importantly, inhibition of the mTOR pathway has already been reported to result not only in anti-senescence but also in anti-atherosclerotic effects [ 177 , 178 , 179 ].…”
Section: Cellular Organelles In Senescent Cellsmentioning
confidence: 99%
“…Moreover, decreased arterial expression of the senescence marker p19, age-associated vascular dysfunction and oxidative stress reversal were observed upon dietary intake of rapamycin [ 277 ]. A recent study also revealed that mTORC1 inhibition mediated by rapamycin strongly weakened replicative senescence in human cardiac progenitor cells [ 177 ], which may open avenues to develop novel therapies. Moreover, statins were reported to inhibit the SASP and participate in the regulation of the cell cycle and telomerase, delaying both EC and T-cell senescence [ 278 ].…”
Section: Senescence-mediated Therapeutic Strategies For Cardiovascmentioning
confidence: 99%